A Study of Project Managers’ Competence Standards in the UAE - Al Ameemi, Hessa Tarish (2011)
This research seeks to determine how the emotional (EQ), managerial (MQ) and intelligent (IQ) competences impact the management process of the various levels of project managers. The study focused upon three levels of project managers: new, traditional and the management of a group of multiple projects (MGMP) project managers. The roles and responsibilities of all three project managers were explained according to Schermerhorn’s (2010) four managerial functions: planning, organizing, controlling and leading. A direct relationship was created between Adair’s (2002) contextual elements (Quality, Knowledge, Functions) of leadership and Crawford’s (2007) competence components specified in Dulewicz and Higgs’s (2005) EQ, MQ and IQ fourteen competences. To test this correlation, qualitative (interviews) and quantitative (survey) techniques were used to collect information from various levels of Ban X project managers. The combination of techniques enabled the researcher to verify that the various elements of the project manger leadership competencies do impact project performance. Following this verification a clear set of recommendations to Bank X project managers were explained along with suggestions for future research.